Titanium‐Carboxylate Metal‐Organic Framework Based on an Unprecedented Ti‐Oxo Chain Cluster - Keum, Yesub; Park, Seonghun; Chen, Ying‐Pin; Park, Jinhee (Angewandte Chemie International Edition, 2018)
Titanium(IV)‐based metal‐organic frameworks (Ti‐MOFs) have received significant attention in recent years due to their numerous photocatalytic applications. We herein prepare the single‐crystalline Ti‐carboxylate MOF (DGIST‐1) composed of an unprecedented Ti‐oxo chain cluster and the porphyrinic ligand, TCPP (tetrakis(4‐carboxyphenyl)porphyrin). Preformed Ti‐oxo clusters were used as Ti4+ sources to avoid the spontaneous hydrolysis and condensation reactions of traditional Ti‐alkoxide precursors, thus, enabling the formation of the highly crystalline Ti‐MOF. The successfully activated DGIST‐1 exhibited a higher surface area (i.e., 1957.3 m2 g−1) than previously reported Ti‐MOFs due to its high crystallinity. Furthermore, the visible‐light‐responsive photocatalytic activity of DGIST‐1 was confirmed by the simultaneous generation of singlet oxygen (1O2) and superoxide (.O2−) species, in addition to the highly efficient and selective oxidation of benzyl alcohol to benzaldehyde. A single‐crystalline Ti‐porphyrinic MOF with an unprecedented Ti‐oxo chain cluster was newly synthesized. The visible‐light‐induced photocatalytic activity of this MOF was demonstrated by its application to the generation of reactive oxygen species and the selective benzyl alcohol oxidation to give benzaldehyde.